Biologic Nurturing Baby Led Feeding to Reduce Pain in Mothers Post Sectio Caesarea - Selviyani, Selviyani; Yuliana, Dewi; Rusminarni, Siti (Sarana Ilmu Indonesia (salnesia), 2025)
One of the nursing problems that often arise in postoperative sectio caesarea patients is an acute inflammatory process and pain that causes discomfort and results in limited movement. One of the non treatments such as lemon aroma therapy, acupressure, guided imagery, autogenic therapy, progressive relaxation therapy, meditation, music therapy and complementary therapy Biologic Nurturing Baby Led Feeding. This study aimed to analyze the effect of Biologic Nurturing Baby Led Feeding on reducing maternal pain post sectio caesarea at Asy-Syifa Medika Tulang Bawang Barat Hospital. This type of research was quantitative research, using pre-experimental using one group pretest-posttest research design. The population in this study was the entire number of sectio caesarea patients at Asy-Syifa Medika Hospital on June 17 - July 21, 2024 there were 30 people. The sampling technique in this study used saturated sampling technique. The Wilcoxon Test result showed a comparison of the pain scale before and after the intervention of Biologic Nurturing Baby Led Feeding with a p-value (0,000) (p-value<0,05), so statistically there is a significant difference in pain scale in Post Sectio Caesarea mothers before and after the intervention of Biologic Nurturing Baby Led Feeding.